Update on Sports Participation for Athletes with Implantable Cardioverter Defibrillators - Lampert,Rachel (2019)
Abstract Prior statements have recommended restriction from competitive sports participation for all athletes with ICDs. Recent data, however, suggests that many athletes can participate in sports without adverse events. In the ICD Sports Registry, 440 athletes, aged 8-60 years, 77 of which were high-level interscholastic athletes, who had continued to practice sports, were prospectively followed for 4 years, with no deaths or failures to defibrillate during practice, and no injuries related to arrhythmia or shock during sports. Shocks did occur, for ventricular and supraventricular arrhythmias. While more athletes received shocks during physical activity than at rest, there were no differences between competition or practice, versus other physical activity. Programming with higher rate cut-offs and longer durations was associated with fewer inappropriate shocks, with no increase in syncope. Based on this study, current recommendations now state that returning to competition may be considered for an athlete with an ICD. In considering this decision, the underlying disease and type of sport should be discussed, and shared decision-making between doctor, patient, and often family, is critical.